2017
DOI: 10.3390/s17122743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composition and Thickness on the Perpendicular Magnetic Anisotropy of (Co/Pd) Multilayers

Abstract: Magnetic materials with perpendicular magnetic anisotropy (PMA) have wide-ranging applications in magnetic recording and sensing devices. Multilayers comprised of ferromagnetic and non-magnetic metals (FM–NM) are interesting materials, as their magnetic anisotropy depends strongly on composition and growth parameters. In this context, (Co/Pd) multilayers have gained huge interest recently due to their robustness and tunable PMA. Here, we report a systematic study of the effect of composition on the magnetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
5
10
0
Order By: Relevance
“…To extract the perpendicular magnetic anisotropy, we used , which gives ≈ 0.06 MJ·m −3 . In a recent work, effective perpendicular anisotropy obtained for Co/Pd multilayes, similar values of PMA were obtained when the Pd layer is thicker than 0.9 nm 40 , 41 . We varied the magnetization saturation M s and magnetic anisotropy to understand the impact of these properties on the skyrmions stability considering a weak Dzyaloshinskii-Moriya below D = 0.8 mJ·m −2 .…”
Section: Introductionsupporting
confidence: 68%
“…To extract the perpendicular magnetic anisotropy, we used , which gives ≈ 0.06 MJ·m −3 . In a recent work, effective perpendicular anisotropy obtained for Co/Pd multilayes, similar values of PMA were obtained when the Pd layer is thicker than 0.9 nm 40 , 41 . We varied the magnetization saturation M s and magnetic anisotropy to understand the impact of these properties on the skyrmions stability considering a weak Dzyaloshinskii-Moriya below D = 0.8 mJ·m −2 .…”
Section: Introductionsupporting
confidence: 68%
“…We first investigated magnetic anisotropy at a pristine Co/Pd interface and further used these results as a reference to understand the origin of magnetic anisotropy changes after hydrogen insertion. In accordance with previous experimental data [32], our calculations showed that Co/Pd trilayers exhibit pronounced magnetocrystalline anisotropy (MCA) with −1.82 mJ/m 2 energy favoring the perpendicular orientation of magnetic moments. The magnetic moment on Co atoms is found to be in the range of 1.76-1.86 μ B , while adjacent Pd also acquires a weak magnetization corresponding to 0.28 μ B per atom, which decays fast with decreasing proximity to the interfacial Co layers [see Fig.…”
Section: A the Origin Of Pma In Co/pd Layerssupporting
confidence: 92%
“…Increasing the number of Co layers diminishes the absolute value of MAE, causing anisotropy reorientation in thicker films, as observed experimentally [32]. The MCA contribution does not show any significant dependence on the number of Co layers, varying in the range of −1.75 to −1.85 mJ/m 2 (see Fig.…”
Section: A the Origin Of Pma In Co/pd Layerssupporting
confidence: 75%
See 2 more Smart Citations